Desensitization of the neuronal insulin receptor: a new approach in the etiopathogenesis of late-onset sporadic dementia of the Alzheimer type (SDAT)? - Henneberg, Nicola; Hoyer, Siegfried (Archives of gerontology and geriatrics, 1995)
Even in its incipient stage, late-onset sporadic dementia of the Alzheimer type (SDAT) is characterized by an abnormal reduction in brain glucose consumption and energy formation. Gathering evidence indicates that cerebral glucose metabolism is controlled by brain insulin/insulin receptors. This led us to hypothesize that the abnormal reduction in glucose utilization found in Alzheimer brains is preceded by a desensitization of cerebral insulin receptors which might be due to enhanced levels of stress factors such as cortisol and catecholamines. The hypothesis is supported by clinical findings of an abnormal response to the oral glucose tolerance test in AD patients. Furthermore, experimental desensitization of the cerebral insulin receptor resulted in both cognitive deficits and metabolic abnormalities in cerebral oxidative glucose metabolism resembling those described in incipient late-onset SDAT. Glucose is the major source of energy in the CNS, and any impairment in cerebral glucose oxidation can be expected to result in deficits in both acetylcholine synthesis and ATP formation, which might contribute to altered APP processing and enhanced susceptibility to neurotoxicity.
Elektronische Reproduktion der Druck-Ausgabe 20. Januar 2000
Gesehen am 25.11.2025